The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1242/jcs.091900
|View full text |Cite
|
Sign up to set email alerts
|

SNAREs, HOPS, and regulatory lipids control the dynamics of vacuolar actin during homotypic fusion

Abstract: SummaryHomotypic vacuole fusion requires SNAREs, the Rab Ypt7p, the tethering complex HOPS, regulatory lipids and actin. In Saccharomyces cerevisiae, actin functions at two stages of vacuole fusion. Pre-existing actin filaments are depolymerized to allow docking and assembly of the vertex ring (a microdomain enriched in proteins and lipids that mediate fusion). Actin is then polymerized late in the pathway to aid fusion. Here, we report that the fusion machinery regulates the accumulation of actin at the verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 58 publications
(64 reference statements)
2
30
0
Order By: Relevance
“…We have previously shown that primed vacuoles stimulate the formation of F-actin in a reaction that is initiated by Cdc42p (26). Vacuoles primed in the presence of narciclasine still maintained normal levels of initial F-actin nucleating activity; however, polymerization activity was not sustained (Fig.…”
Section: Analysis Of Eef1a Subdomains For Rho1pmentioning
confidence: 81%
See 1 more Smart Citation
“…We have previously shown that primed vacuoles stimulate the formation of F-actin in a reaction that is initiated by Cdc42p (26). Vacuoles primed in the presence of narciclasine still maintained normal levels of initial F-actin nucleating activity; however, polymerization activity was not sustained (Fig.…”
Section: Analysis Of Eef1a Subdomains For Rho1pmentioning
confidence: 81%
“…The Rho1p-eEF1A interaction likely has functional implication in regulating actin remodeling coupled to vacuolar fusion because actin is enriched at the "vertex ring" of membranes during vacuolar docking, and actin remodeling is required for the terminal step leading to vacuolar membrane fusion (10,26). Therefore, we hypothesize that eEF1A is recruited to vacuoles from the cytosol by Rho1p and may mediate Rho1p signaling for actin reorganization.…”
mentioning
confidence: 94%
“…Others have found that Ycf1p physically interacts directly with Rho1p, a GTPase associated with actin dynamics (40). Because Rho1p (41), actin (42,43), and PI3P (3) play important roles in vacuole fusion, we examined the effect of deleting YCF1 and other ABCC transporters on vacuole fusion. We found that ycf1⌬ and bpt1⌬ vacuoles were each attenuated for fusion, yet the double deletion did not exhibit additive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several regulators have been identified that lie outside of the core fusion machinery including the class-1 casein kinase Yck3, [22][23][24] the phosphatidic acid (PA) phosphatase Pah1, 25 the PI 3-kinase Vps34, 26 the Na C /H C exchanger Nhx1, 27 phospholipase C, 28 Rho GTPases, 29 and actin. 30,31 In the search for new regulators of vacuole fusion we have now turned to class C ABC transporters as inspired by the work of others. Recent work has demonstrated that ABC transporters, which are well characterized as proteins that detoxify the cell of metals, bile acids and other toxins, can also regulate vacuole homeostasis.…”
Section: Membrane Fusionmentioning
confidence: 99%
“…Previous studies have shown that vacuolar actin undergoes remodeling during the fusion reaction. 30,31 Early in the pathway filamentous actin depolymerizes which could facilitate the lateral movement of proteins to the vertex microdomain. Late in the pathway globular actin polymerizes, where it could potentially serve as a molecular fence to stabilize protein complexes into small domains such as the vertex ring.…”
Section: Ycf1 and Fusionmentioning
confidence: 99%